TESTIMONIANZE Dl ATTIVITA' TETTONICA TARDOTRIASSICA NELLE PREALPI VICENTINE (Rivista italiana di Paleontologia e Stratigrafia, 2020)
In the Recoaro area (Northern Italy) a channelized breccia containing abundant metamorphic clasts of the crystalline basement is interbedded in the Iower part of the Dolomia Principale formation (Upper Triassic) The breccia is interpreted as a fluvial deposit, which momentarily interrupted the cyclic sedimentation of the Dolomia Principale. This event is connected with a local tectonic phase The instability rnay be related to a more important tectonic activity which involved a region located South of the Recoaro area.